(untitled) (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2022)
Toxocariasis in dogs is caused by infection of Toxocara canis. The disease is not recognized and often underestimated by the owners. Toxocara canis is a pathogenic gastrointestinal worm and the larva could infect the internal organs, which cause diarrhea and kill the animals if the disease is not seriously handled. Toxocara canis is not only danger to the animals but it could also infect the human being. The purpose of this study was to identification Toxocara canis on puppy in Makassar Pet Clinic. Feces samples were collected from 31 puppies in Makassar Pet Clinic. Feces were examined by native method and floating method to detected eggs of Toxocara canis based on their morphology. The result showed 5 samples were identified positive of Toxocara canis and 26 samples were negative of Toxocara canis Keywords: Toxocariasis, Toxocara canis, Endoparasite, Puppy